Gender Bias in Javanese Society: A Study in Language Forms Choice to Men and Women - Atmawati, Dwi (Humaniora, 2018)
This research aimed to reveal different ways of thinking of society for men’s and women’s positions from the sociolinguistic point of view to accomplish the previous research. The research was conducted by studying language data in sentence formation on short story (fiction) and article (nonfiction). The short story and article used as data sources originated from internet media. This research used a qualitative descriptive method. The data were analyzed using equality and distributional methods. The finding data are classified into two: language form choice difference is based on linguistic factor and non-linguistic factor. Linguistic factor includes morphology, lexicon, phrase, compounds words, idiom. Non-linguistic factor includes the use of husband’s and wife’s names; call of husband’s name after wife’s proper name. The research shows that gender bias in Javanese society is expressed in differences in language forms choice to men and women. The language forms obtained from the data covers differences in language forms choice as caused by a social way of thinking to men’s and women’s status in daily life.